Optimal placement and sizing of battery energy storage system considering the duck curve phenomenon - Wong L.A.; Ramachandaramurthy V.K.; Walker S.L.; Ekanayake J.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Location; Particle swarm optimization (PSO); Secondary batteries; Battery energy storage systems; Distribution systems; Energy storage systems; Exploration and exploitation; Location and sizings; Meta heuristic algorithm; Optimal placement and sizings; Particle swarm optimisation; Energy storage